Long-and short-run climate impacts on Brazil: theory and evidence for agriculture and health - Pereda, Paula Carvalho (2012)
Climate has relevant impacts on economic activities and human well-being. This study aims to contribute to the identification and measurement of these impacts on the agricultural markets and health. With regard to health, dengue fever - a climate-sensitive disease - is analyzed, as it affects thousands of Brazilians every year, generating large costs in both private and public markets (approximately US$800 million in Brazil in 2011). Thus, chapter 2 addresses the impact of climate on the risk of dengue fever in Brazil, modeling dengue incidence as a risk function estimated using count data models applied to the outbreak of dengue epidemics in 2010 and controlling for likely endogeneities. The results corroborate the relevance of climate variables in explaining dengue incidence in Brazil. Moreover, if climate change occurs as expected, the results suggest a potential added risk for central-southern areas in Brazil and a risk reduction for northern areas of the country. Short-term deviations from normal rainfall conditions in summer also seem to increase the risk of dengue when compared to normal rainfall conditions. Other results suggest the non-effectiveness of local expenditures for epidemiological surveillance and the need of integrated actions to control the disease. When it comes to agricultural markets, two important hypotheses are tested: i) farmers only observe the average climate conditions of their region when deciding the type and amount of crop/animal to grow/raise (Chapter 3); ii) weather diversions from normal climate conditions might deviate farmers from their optimal profits, causing inefficiencies (Chapter 4). Both hypotheses are not rejected by the data. The modeling approach used is the translog profit frontier approach. The results indicated that if the climate change forecasts are confirmed, almost all the agricultural products in Brazil will be negatively affected, especially production of cattle products (beef and milk), coffee and maize. The only product that shows a positive effect is soybeans, probably due to its current high adaptability to different climate patterns. Use of irrigation is the main compensation instrument to reduce the expected climate change impacts. However, technological instruments such as use of transgenic seeds, cattle confinement, along with the increase in tillage, are also important adaptation measures to climate change. The analysis of the determinants of the efficiencies calculated suggests that droughts and cold stresses cause harmful effects to agriculture in Brazil. In 2006, the estimated loss from rainfall anomalies is approximately 15 billion dollars (in 2011 values). The southern and midwestern regions are slightly more vulnerable than the other regions. Assuming the extreme hypothesis of drought and cold stress occurrence overall in Brazil, the total profit loss is about 81 and 35 billion dollars, respectively. These losses can be mainly mitigated by the intense use of an insurance instrument, but the participation of farmers in the agricultural insurance market in Brazil is still very low.